Hydro-processing of palm fatty acid distillate for diesel-like hydrocarbon fuel production using La-zeolite beta catalyst - Nur Azreena, I.; Asikin-Mijan, N.; Lau, H. L.N.; Hassan, M. A.; Izham, S. Mohd; Kennedy, E.; Stockenhuber, M.; Yan, P.; Taufiq-Yap, Y. H. (Elsevier B.V., 2024)
Green diesel produced from palm fatty acid distillate (PFAD) could decrease reliance on fossil fuels and GHG emissions. Thus, this work reports a solventless hydrodeoxygenation (HDO) reaction using zeolite beta and La-zeolite beta (LZ) to convert PFAD into diesel-rich fuel. Specifically, LZ-catalyzed reaction dominated the hydrocarbon fraction over zeolite beta with high HDO and DO activity. Lewis' acid sites remove oxygenated species, while Brønsted acid sites aid in cracking. Since most HDO reactions happened on LZs' exteriors, pore size did not affect HDO. The HDO optimum reaction activity was attained at 400 °C using 1 wt% of LZ under 5 MPa H2 pressure within 3 h. LZ showed 84 % diesel selectivity and greater hydrocarbon output in the N2 flow environment (DO reaction) than the H2-reaction conditions. The H2 atmospheric reaction system prevented LZ coking, confirming its effect on catalyst stabilisation. The HDO process yielded a paraffinic hydrocarbon product with ∼73 % selectivity of hexadecane (C16H34), demonstrating the formation of liquid fuel with reduced oxygenates. A vacuum distillation technique purified the crude liquid product (CLP) into a refined liquid product (RLP) with 99 % diesel component renewable diesel (RD 100) met ultra-low sulfur diesel requirements that closely resemble those derived from petroleum. This affirms that the high-quality R100 can be used in existing diesel engines efficiently without modifications. Based on reusability studies, the LZ catalysts are capable of performing HDO and DO for up to 5–6 cycles, proving their positive impact on process efficiency and catalyst longevity. Overall, the LZ-catalyzed hydrogen-assisted process is a more promising technology for the oil and gas industry, where hydrogen can be produced from various refinery feedstocks, hence, its implementation could significantly enhance efficiency and sustainability in refining operations.